ISMO Applications in Maintenance Planning for Biogas- Producing Organic Waste Machines - Rahayu Mekar Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
The use of alternative energy sources is a solution to the limited fossil fuel supply. This renewable energy must become new energy such as solar power, wind power, biogas and others. Biogas is another source of electricity in the form of flammable gas produced during the decomposition of organisms by anaerobic organisms or organisms that can survive in confined space conditions. Organic waste biogas production equipment is a tool that supports biogas production by various decomposition processes. In order for the biogas generator to always work properly and be ready for use, there must be a maintenance plan for the device. When planning the maintenance of machinery producing biogas from organic waste, the ISMO method should be followed in the following steps, such as defining maintenance tasks and scheduling maintenance. Machine maintenance is a process to maintain and maintain the machine for a long time. Its function is to ensure the normal operation of the machine and good operation during use, the life of the machine is long, and the machine does not need to be repaired quickly, which can reduce the maintenance cost as much as possible. . The results of the study using this method show that a biogas machine with 200 liters of organic waste capacity requires 9 inspections, 6 minor repairs and 2 medium repairs.